Effect of Artificial Intelligence on Job Market - Xiong Binran (SHS Web of Conferences, 2024)
This article focuses on the possible impacts of AI robotics on job market and how to deal with it. The development of AI is not the first time in history when labour market faces huge restructure due to new technology inventions, the question is what the past tells about the future. The fear of AI robotics substituting human workforce remarkably resembles the “industrial revolution” when steam engines, looms and cotton gins were first invented, millions of labours across Europe and North America were under threat of unemployment. The result of industrial revolution turned out to be not as devastating as people worried, the transition in economy from handicrafts and agriculture to machine manufactory not only increased productivity but also more jobs and higher wages. By comparing the statistics and differences between AI and industrial revolution, the result again shows that despite the huge impact on unemployment in the short term, the long-term effects are positive. The fear of AI is unnecessary as long as the government seeks to post reasonable regulations on machines and subsidize the structural unemployment workers.